2013
DOI: 10.1186/1744-8069-9-52
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nav1.8 and Nav1.9 Sodium Channel Expression with Neuropathic Pain in Human Subjects with Lingual Nerve Neuromas

Abstract: BackgroundVoltage-gated sodium channels Nav1.8 and Nav1.9 are expressed preferentially in small diameter sensory neurons, and are thought to play a role in the generation of ectopic activity in neuronal cell bodies and/or their axons following peripheral nerve injury. The expression of Nav1.8 and Nav1.9 has been quantified in human lingual nerves that have been previously injured inadvertently during lower third molar removal, and any correlation between the expression of these ion channels and the presence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 52 publications
4
35
0
1
Order By: Relevance
“…To determine the abundance ratio of Schwann cells, the area of immunoreactivity against anti-S100β antibodies was measured using ImageJ software in three fields of view from the central side of the traumatic neuroma to the peripheral side. The abundance ratio of Schwann cells in each sample was calculated as the average of the immunoreacted area against anti-S100β antibodies per tissue area in three fields of view [23][24][25].…”
Section: Quantification Of Schwann Cells In Traumatic Neuroma Samplesmentioning
confidence: 99%
“…To determine the abundance ratio of Schwann cells, the area of immunoreactivity against anti-S100β antibodies was measured using ImageJ software in three fields of view from the central side of the traumatic neuroma to the peripheral side. The abundance ratio of Schwann cells in each sample was calculated as the average of the immunoreacted area against anti-S100β antibodies per tissue area in three fields of view [23][24][25].…”
Section: Quantification Of Schwann Cells In Traumatic Neuroma Samplesmentioning
confidence: 99%
“…Earlier, the Na v 1.8 channel subtype also was found in trigeminal ganglia. 17 Na v 1.8 as well as the coexpressed Na v 1.7 are enriched in thin peripheral trigeminal neurons 35,36 and dorsal root ganglia (DRG), 37 but of particular importance also in gingival tissue of patients suffering from trigeminal neuralgia 8 (Table 2). Both subtypes are blocked by ambroxol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found the up-regulation of Nav1.8 in trigeminal nerve [25][26][27]. As the trigeminal root is compressed, the nerve fibers are demyelinated, which induces the Nav1.8 emerge in the compressed site and leads to subthreshold membrane potential oscillation (SMPO); when the membrane potential reaches the threshold, ectopic action potentials are ignited; when these messy impulses transmit to the central, paroxysmal pain attacks [28].…”
Section: Discussionmentioning
confidence: 99%